Meniscal Scaffolds: a Mini Review - Koukoulias NE; Dimitriadis T; Germanou E; Papavasileiou AV; Sinopidis C (Journal of Surgery and Surgical Research - Peertechz Publications, 2015)
Partial meniscal defects can be the cause of knee joint line pain. Synthetic meniscal scaffolds have been used as substitutes for the meniscal defect. CMI (Collagen Meniscus Implant, Ivy Sports Medicine, Gräfelfing, Germany) was the first product designed and Actifit (Orteq Bioengineering, London, United Kingdom), a polyurethane scaffold, is a more recent one. Both implants have been proven safe and clinically efficient so far. The indications, surgical technique, postoperative regime, results and complications are discussed.